The impact of DG's location on the small signal stability of the distribution network. Issue 4 (February 2019) - Zhang, Shaohui; Bao, Wei; Xu, Jiadong; Han, Xueshan; Wang, Mingqiang; Yan, Yuehao; Fu, Xiaoyong
Abstract: The distribution network has been integrated with more and more distributed generations. Most of these generations are inverter based photo-voltaic plant or DFIG based wind farm. As the proportion of these renewable energies goes high, the stability problems, especially the small signal stability problems gain attention from researchers. Literatures have conducted on the single machine infinite bus system of them, focusing mostly on their dynamic characteristics. This paper analyses the impact of DG's location on the small signal stability of the distribution network, which includes DGs, network and dynamic load. The conclusion is drawn from the modal analysis, and is verified by time domain simulation.